VPS35-deficiency results in an impaired AMPA receptor trafficking and decreased dendritic spine maturation. Issue 1 (December 2015) - Tian, Yun; Tang, Fu-Lei; Sun, XiangDong; Wen, Lei; Mei, Lin; Tang, Bei-Sha; Xiong, Wen-Cheng
Abstract Background Vacuolar protein sorting 35 (VPS35), a key component of retromer, plays an important role in endosome-to-Golgi retrieval of membrane proteins. Dysfunction of VPS35/retromer is a risk factor for neurodegenerative disorders, including AD (Alzheimer's disease) and PD (Parkinson's disease). However, exactly how VPS35-deficiency contributes to AD or PD pathogenesis remains poorly understood. Results We found that VPS35-deficiency impaired dendritic spine maturation and decreased glutamatergic transmission. AMPA receptors, GluA1 and GluA2, are significantly reduced in purified synaptosomal and PSD fractions from VPS35-deficient brain. The surface levels of AMPA receptors are also decreased in VPS35-deficient neurons. Additionally, VPS35 interacted with AMPA-type receptors, GluA1 and GluA2. Overexpression of GluA2, but not GluA1, could partially restore the spine maturation deficit in VPS35-deficient neurons. Conclusions These results provide evidence for VPS35's function in promoting spine maturation, which is likely through increasing AMPA receptor targeting to the postsynaptic membrane. Perturbation of such a VPS35/retromer function may contribute to the impaired glutamatergic transmission and pathogenesis of neurodegenerative disorders, such as AD and PD.